Characterization of the drug-to-antibody ratio distribution for antibody–drug conjugates in plasma/serum. (May 2013) - Xu, Keyang; Liu, Luna; Dere, Randall; Mai, Elaine; Erickson, Rebecca; Hendricks, Angela; Lin, Kedan; Junutula, Jagath R; Kaur, Surinder
Background: Antibody–drug conjugates (ADCs) are a new class of cancer therapeutics that deliver potent cytotoxins specifically to tumors to minimize systemic toxicity. However, undesirable release of covalently linked drugs in circulation can affect safety and efficacy. The objective of this manuscript was to propose and assess the assays that allow for the characterization of the drug deconjugation in plasma/serum.Results: ADCs of three main drug conjugation platforms, linked via lysine, site-specific engineered cysteine or reduced interchain disulfide cysteine residues, were analyzed using affinity capture for sample enrichment coupled with LC–MS or hydrophobic interaction chromatography–UV for detection. These novel approaches enabled measurement of the relative abundance of individual ADC species with different drug-to-antibody ratios, while maintaining their structural integrity.Conclusion: The characterization data generated by affinity capture LC–MS or hydrophobic interaction chromatography–UV provided critical mechanistic insights into understanding the stability and bioactivity of ADCs in vivo, and also helped the development of appropriate quantitative ELISAs.